2015
DOI: 10.1111/bcp.12667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carboxylesterase 1 c.428G > A single nucleotide variation on the pharmacokinetics of quinapril and enalapril

Abstract: AIMThe aim of the present study was to investigate the effects of the carboxylesterase 1 (CES1) c.428G > A (p.G143E, rs71647871) single nucleotide variation (SNV) on the pharmacokinetics of quinapril and enalapril in a prospective genotype panel study in healthy volunteers. METHODSIn a fixed-order crossover study, 10 healthy volunteers with the CES1 c.428G/A genotype and 12 with the c.428G/G genotype ingested a single 10 mg dose of quinapril and enalapril with a washout period of at least 1 week. Plasma concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 40 publications
4
36
2
Order By: Relevance
“…This is in contrast to our MPH study, in which a markedly (149%) and highly significant increase in d-MPH AUC was found compared to the control group indicating decreased metabolizing capacity [14]. In a recent human study, Tarkiainen et al [12] investigated the impact of the 143E allele on the metabolism of quinapril and enalapril. Both drugs were administered as single 10 mg doses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to our MPH study, in which a markedly (149%) and highly significant increase in d-MPH AUC was found compared to the control group indicating decreased metabolizing capacity [14]. In a recent human study, Tarkiainen et al [12] investigated the impact of the 143E allele on the metabolism of quinapril and enalapril. Both drugs were administered as single 10 mg doses.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent human study, Tarkiainen et al . investigated the impact of the 143E allele on the metabolism of quinapril and enalapril. Both drugs were administered as single 10 mg doses.…”
Section: Discussionmentioning
confidence: 99%
“…Duplication of the gene is the reason for the observed copy number variation . The CES1 G143E variant is the best‐documented polymorphism having an impact on the metabolism of various CES1‐dependent drugs in vivo . Other SNPs have been associated with impaired CES1 activity but not to the same extent as G143E …”
Section: Introductionmentioning
confidence: 99%
“…6,7 The CES1 G143E variant is the best-documented polymorphism having an impact on the metabolism of various CES1-dependent drugs in vivo. [8][9][10][11][12] Other SNPs have been associated with impaired CES1 activity but not to the same extent as G143E. 13,14 The activity of drug-metabolising enzymes can be estimated by calculating the ratio between the parent drug and its metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…), antiplatelets (clopidogrel), antiviral agents (oseltamivir), central nervous system agents (e.g., meperidine, cocaine) and anticancer agents (capecitabine) [10]. Polymorphisms in CES1 gene can significantly reduce hydrolysis of enalapril but not quinapril [11]. On the other hand, CES1 genetic polymorphism did not affect the hydrolysis of oseltamivir in healthy Japanese subjects [12].…”
Section: Discussionmentioning
confidence: 99%